1996
DOI: 10.1046/j.1365-2249.1996.d01-641.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of glycosaminoglycans (GAGs) in regulation of the immunogenicity of human vascular endothelial cells

Abstract: SUMMARYHeparan sulphate is a common glycosaminoglycan component of proteoglycans present on the luminal surface of vascular endothelium. It has been proposed that an important function of these molecules is the sequestration of a range of proinflammatory and proadhesive cytokines. Such cytokines play a vital role during lymphocyte recruitment from the blood at sites of inflammation. In this study it is shown that the effects of interferon-gamma (IFN-°), but not of tumour necrosis factor-alpha (TNF-®), are inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…The capacity of heparin and of HS to antagonize the induction of class II MHC antigens by IFN-g-treated EAhy.926 is entirely consistent with the results of previous studies using cultured HUVEC [19,20]. Furthermore, this effect was not produced by the galactosamine-containing molecules CS-A or CS-C.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The capacity of heparin and of HS to antagonize the induction of class II MHC antigens by IFN-g-treated EAhy.926 is entirely consistent with the results of previous studies using cultured HUVEC [19,20]. Furthermore, this effect was not produced by the galactosamine-containing molecules CS-A or CS-C.…”
Section: Discussionsupporting
confidence: 89%
“…For example, the proadhesive activity of chemokines such as RANTES and MCP-1 is blocked by heparin [18]. Previous studies by this group [19,20] and others [21] have shown that heparin can also antagonize the activity of IFN-g.…”
Section: Introductionmentioning
confidence: 99%
“…Both play important roles in wound healing by activating epidermal cells and fibroblasts to form granulation tissue, mediate angiogenesis, and chemoattract macrophages and fibroblasts (133)(134)(135). In a feedback mechanism, cathelicidin from activated leukocytes in pigs (PR-39) has shown a direct influence on dermal fibroblasts by increasing synthesis of the extracellular matrix proteoglycans, syndecan-1 and -4 (136), which are required for the activity of many growth factors (137)(138)(139)(140). In an animal model, syndecan production was delayed and ineffective wound repair (141,142) was reported.…”
Section: Host Defense Peptides In Woundsmentioning
confidence: 99%
“…HS, the constituent of up to 50% of the total expressed GAG in endothelial cells [17], is unique among GAGs in the ability to bind a large number of different proteins with complex role in the extracellular matrix, regulating a wide variety of biological process, including hemostasis, inflammation, angiogenesis, growth factors, cell adhesion [18], as well as serine proteinase-mediated tissue remodeling [19]. In the placenta, the endothelium functions as the interface between blood and the tissues and must be able to respond dynamically to its microenvironment in order to regulate the passage of cells into sub-endothelial tissues [20]. Therefore, the regulation (up or down) of the extent of HS sulfation within the endothelial microenvironment might represent a mechanism for balanced homeostasis in the developing placenta.…”
Section: Introductionmentioning
confidence: 99%